2013
DOI: 10.1680/geot.11.p.068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation by limit analysis on the stability of slopes with cracks

Abstract: A full set of solutions for the stability of homogeneous c, φ slopes with cracks has been obtained by the kinematic method of limit analysis, providing rigorous upper bounds to the true collapse values for any value of engineering interest of φ, the inclination of the slope, and the depth and location of cracks. Previous stability analyses of slopes with cracks are based mainly on limit equilibrium methods, which are not rigorous, and are limited in their capacity for analysis, since they usually require the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 20 publications
2
90
0
3
Order By: Relevance
“…The formation of two cracks is observed. Cracks can significantly reduce slope stability [28]. Through the analysis the location of each crack and failure mechanism can be tracked, the deformation of the slope and the velocity of the sliding mass can be calculated.…”
Section: Preliminary Testsmentioning
confidence: 99%
“…The formation of two cracks is observed. Cracks can significantly reduce slope stability [28]. Through the analysis the location of each crack and failure mechanism can be tracked, the deformation of the slope and the velocity of the sliding mass can be calculated.…”
Section: Preliminary Testsmentioning
confidence: 99%
“…6). The calculation of the external work in this case of a composite partly log-spiral partly linear failure surface requires the calculation of the work done by the fictitious wedge BOCADB minus the work of the fictitious wedge DCAD (Utili 2013). The analytical expressions for the calculation of the external work done by soil masses sliding along composite log-spiral failure surfaces, which requires the use of fictitious wedges bordered by a log-spiral, was first presented in Utili (2005) and Utili and Nova (2008) for the case of slopes with a horizontal upper part subject to a sequence of landslides, and in Utili and Crosta (2011) for the more general case of slopes with an inclined upper part.…”
Section: Calculation Of the External Rate Of Work For Rotational Failmentioning
confidence: 99%
“…In the search for the failure mechanism of a slope of given inclination and friction angle (␤ and , respectively), the length and location of the crack is free, i.e., the minimization of the function is sought over four independent variables, the angles 0 , h , C (in Utili (2013) the angles , , and are employed with = 0 , = h , and = D ), and ␤= with the additional constraint that "the crack cannot be deeper than the maximum depth of the crack discussed." Concerning the variable ␤=, the discusser has shown that for > 5°, all the failure mechanisms pass through the slope toe, i.e., ␤= = ␤, whatever values of ␤ and are considered (Utili 2013), so that for the drained analyses presented in the paper under discussion with = 10°or greater, the number of variables to be considered in the unconstrained minimization can be reduced to three: 0 , h , and C .…”
Section: Failure Mechanisms For Pre-existing Cracksmentioning
confidence: 99%
See 2 more Smart Citations